From writing to composing: an introductory composition course for students of english - Ingram, Beverly; Carol King (New York: Cmbridge University Press, 1995)
Este texto contiene los siguientes capitulos: Getting started, getting acquainted, getting into a routine, describing places, describing people, describing peopless lives
Keywords: Lenguaje - Inglés